Inoculation with arbuscular mycorrhizal fungi at the seedling stage of potatoes improves phosphorus use efficiency - Liu, Xiaoyu; Yu, Jing; Wei, Jie; Qin, Yonglin; Shi, Xiaohua; Liu, Kun; Jia, Liguo; Fan, Mingshou (Frontiers in Sustainable Food Systems, 2025)
In potato production, relatively low phosphorus use efficiency (PUE) leads to excessive phosphorus (P) fertilizer application in many regions, resulting in increasingly environmental risks. Consequently, an increasing number of researchers have started to explore the ways to improve the PUE. The symbiosis between arbuscular mycorrhizal fungi (AMF) and crop roots enhances P uptake. However, the effectiveness of AMF inoculation under field conditions depends on the environment and agronomic managements. In Inner Mongolia, China, few field experiments have been conducted on AMF inoculation in potato production. This is mainly due to low estimates of AMF colonization attributed to fungicide use in seed tuber treatments and soil mechanical disturbance caused by ridging. This study aimed to test whether inoculation with AMF after ridging at the seedling stage could improve AMF colonization in potatoes, thereby enhancing P uptake and tuber yield. Field experiments were conducted in Inner Mongolia to compare the effects of AMF inoculation after ridging at seedling stage versus inoculating seed potato with AMF during sowing, and to investigate the potential of reducing the P application rate through inoculation with AMF in potato production. The AMF colonization rate, soil hyphal density, P uptake, plant growth and tuber yield of potatoes under different treatments were measured. The results showed that compared with AMF inoculation at sowing, inoculation after ridging at the seedling stage significantly increased AMF colonization by 8 percentage points. This led to a significant improvement in P uptake and potato growth, ultimately resulting in a yield increase of approximately 6%. Further findings showed that reducing P application by 25% from the conventional rate (160 kg P2O5 ha−1) led to significant yield loss. Whereas with AMF inoculation at the seedling stage, yield levels were maintained and the partial factor productivity of P fertilizer (PFP) was increased by an average of 39%. In conclusion, this study reveals that AMF inoculation after ridging can mitigate the negative impacts of fungicides in seed tuber treatment and ridging-caused soil disturbance on AMF colonization. It highlights importance of inoculation timing for achieving higher AMF population density. Moreover, the study demonstrates that the developed AMF inoculation enables a reduction of P fertilizer application in potato production. This provides a viable approach to enhance PUE and promote sustainable potato production in areas such as Inner Mongolia. It carries significant agronomic and environmental implications.